2015
DOI: 10.1371/journal.pone.0121126
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Sterile Insect Technique with the Incompatible Insect Technique: I-Impact of Wolbachia Infection on the Fitness of Triple- and Double-Infected Strains of Aedes albopictus

Abstract: The mosquito species Aedes albopictus is a major vector of the human diseases dengue and chikungunya. Due to the lack of efficient and sustainable methods to control this mosquito species, there is an increasing interest in developing and applying the sterile insect technique (SIT) and the incompatible insect technique (IIT), separately or in combination, as population suppression approaches. Ae. albopictus is naturally double-infected with two Wolbachia strains, wAlbA and wAlbB. A new triple Wolbachia-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
163
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(173 citation statements)
references
References 50 publications
3
163
0
7
Order By: Relevance
“…Current targets for IIT include Ae. albopictus through the generation of a triple Wolbachia -infected strain ( w AlbA, w AlbB, and w Pip infected) [99] and Ae. polynesiensis , a vector of lymphatic filariasis in the South Pacific [100].…”
Section: Releasing Mosquitoes For Disease Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Current targets for IIT include Ae. albopictus through the generation of a triple Wolbachia -infected strain ( w AlbA, w AlbB, and w Pip infected) [99] and Ae. polynesiensis , a vector of lymphatic filariasis in the South Pacific [100].…”
Section: Releasing Mosquitoes For Disease Controlmentioning
confidence: 99%
“…In addition, the fitness of three Ae. albopictus strains (triple-infected, double-infected, and uninfected) of the same genetic background revealed that the presence of Wolbachia had only minimal effects on host fitness [99]. Irradiation with a female-sterilizing dose had no negative impact on the longevity of triple infected males, while a reduced lifespan was seen in wild type males ( w AlbA and w AlbB) irradiated with a higher male-sterilizing dose [103].…”
Section: Releasing Mosquitoes For Disease Controlmentioning
confidence: 99%
“…In mosquitoes, Wolbachia can induce CI, which causes a decrease or absence of brood hatch when infected males mate with females that are uninfected or infected with a different Wolbachia type (Sinkins 2004). Individuals can be infected with one or more Wolbachia strains (i.e., superinfections), and as an example of unidirectional CI, doubleinfected females can be incompatible with triple-infected males, producing no or reduced progeny, while the reciprocal cross is compatible producing normal progeny (Fu et al 2010, Zhang et al 2015.…”
mentioning
confidence: 99%
“…albopictus populations via unidirectional CI, it is hypothesized that a mosquito strain that is triple infected with Wolbachia would be required, such that unidirectional CI occurs in crosses with wild-type Ae. albopictus (Fu et al 2010, Zhang et al 2015.…”
mentioning
confidence: 99%
“…This strategy is presently tested in a pilot trial in Thailand against Aedes aegypti (P. Kittayapong, personal communication) and in China against Ae. albopictus (Zhang et al 2015).…”
Section: The Incompatible Insect Techniquementioning
confidence: 99%